Valuatios of innovative ICT activities in enviromental eucation by training teachers - Brero-Peinado, Vito Battista; Acebal, María del Carmen (My University, 2019)
In a training proposal, consisting of five phases which are divided into two roles for the Pre service Secondary Science Teacher (PSST) -firstly, in the role of student, and secondly in the role of PSST- this work analyzes, according to the second role, the evaluations carried out by the PSST from the Master's Degree in Teacher of Science Education (MDTSE) at the University of Málaga (Spain) on ICT activities, using the annotations on video in a significant environmental situation. Regarding these evaluations, they had to identify contents and educational competences, as well as highlight and argue the advantages and disadvantages of the annotations on video as a teaching resource. The results show a majority tendency to associate the contents with ecological sciences over environmental sciences; for its part, the most frequently cited competition is that of science and technology. Finally, the development of digital skills and the motivating component stand out as advantages.
Keywords: Ciencias experimentales - Estudio y enseñanza; Maestros - Formación; Initial Teacher Education (Pre service); Society and Environment Education; ICT Enhanced Teaching and Learning.